Principal’s Managerial Roles in Adapting the Operational Curriculum (KOSP) of the Merdeka Curriculum: A Case Study of an Elementary School in a Tidal Water Area of Indonesia - Aryo Handhoko; Nila Kesumawati; Mulyadi Mulyadi (Journal of Social Work and Science Education, 2026)
This study examines the principal’s managerial functions planning, implementation, and evaluation in adapting the Operational Curriculum of Educational Units (KOSP) within the Merdeka Curriculum at SDN 3 Karang Agung Ilir, an elementary school located in a tidal-water area of South Sumatra, Indonesia. Using a qualitative single holistic case study design under an interpretive naturalistic paradigm, data were collected through observation, in-depth interviews with nine informants (principal, teachers, committee members, supervisor, parents), and document analysis. The interactive model of Miles, Huberman, and Saldaña guided data analysis. Findings reveal that while the principal fulfilled formal managerial roles in drafting KOSP documents, mobilizing teachers, and conducting supervision, the planning remained generic and insufficiently contextualized to tidal-area challenges. Implementation largely mirrored the 2013 Curriculum, with minimal integration of local environmental and socio-economic realities. Evaluation focused on administrative compliance rather than curriculum effectiveness or data-driven improvement. These findings indicate that the flexibility of the Merdeka Curriculum remains underutilized in extreme geographic contexts. This study contributes an empirical model of “guided imitation” and a procedural-but-immature evaluation system, extending curriculum management theory to tidal-water schools. Implications suggest the need for context-sensitive KOSP indicators, structured in-house training, and participatory evaluation involving fishing communities.